Peran Layanan Bimbingan Klasikal dan Kelompok terhadap Motivasi Belajar Siswa SMA - Christiana, Elisabeth; Shafira, Rizka Rusydah Reza; Habibah, Noviana; Maharani, Meutya Faiha Adila (Lembaga Yasin AlSys, 2025)
Learning motivation is an important factor in student success. This research aims to examine in depth the role of classical and group guidance services in improving high school students’ learning motivation through literature studies. Through the analysis of various journals, it is expected to specifically identify the influence of the two types of guidance services on various aspects of student learning motivation, such as intrinsic, extrinsic, and learning goal motivation. In addition, this research will also identify the role of classical and group guidance services that can modulate the effectiveness of these guidance services. The results of this literature review are expected to make theoretical and practical contributions to the development of guidance programs in schools, as well as provide recommendations for educators and counselors in an effort to increase students’ learning motivation.